Implementasi Akad Murabahah pada Pembiayaan KUR (Kredit Usaha Rakyat) dalam Pengembangan Usaha Mikro Bank Syariah Indonesia KCP Mojokerto Mojosari - Siti Firdatun Najwa; Lu’lu’il Maknuun (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to understand how the KUR financing mechanism using murabahah contracts is implemented by Bank Syariah Indonesia and its role in the development of micro enterprises. The research approach used is qualitative with a descriptive method. Research data was collected through in-depth interviews, direct observation, and documentation. The results of the study show that the murabahah contract is effectively applied in KUR financing at Bank Syariah Indonesia KCP Mojokerto Mojosari. This agreement allows banks to buy goods needed by customers and then sell them to customers with an agreed profit margin. The implementation of this murabahah contract provides an alternative financing that is in accordance with sharia principles, thus attracting the interest of micro entrepreneurs who want to avoid usury. In addition, this financing mechanism has also been proven to help increase production capacity and the economic welfare of micro business owners. This study found that the implementation of KUR financing through murabahah contracts at Bank Syariah Indonesia KCP Mojokerto Mojosari contributed significantly to the development of micro businesses. Micro-entrepreneurs who obtain this financing can expand their business, improve product quality, and expand the market. Thus, this financing not only helps in the provision of working capital but also encourages local economic growth.